The Slavonic Translation of the Apocryphal Didascalia "Domini/Revelation to the Holy Apostles" (BHG 812 A-E) - Райнхарт, Йоханнес (Studia Ceranea, 2014)
The New Testament apocryphon Didascalia Domini is one of the least known. Its original was written in Greek, according to François Nau, at the end of the 7th century. Relatively early it was translated into Old Church Slavonic. At present five copies of this translation are known, stretching from the 13th to the 15th century. Three of them belong to the Serbian redaction, one each to the Russian (East Slavic) and to the Middle Bulgarian redaction. According to Michail Nestorovič Speranskij the translation originated in Bulgaria. The Greek copies, the oldest of which stems from the 11th century, have divergent final chapters. Moreover, the Slavic translation has yet another ending not corresponding to any of the Greek texts. The textological analysis of the five Slavic copies makes it possible to get an idea of their mutual relationship. On the basis of the linguistic archaisms of the text one can surmise that the translation has been made in Eastern Bulgaria during the 11th century. At the end of the paper there is a critical edition of the Slavic text.